Emulsification Characteristics of Rhamnolipids by Pseudomonas aeruginosa Using Coconut Oil as Carbon Source (Journal of Environmental Microbiology and Toxicology, 2018)
Rhamnolipids (RLs) production using coconut oil as a carbon source by the bacterium P. aeruginosa is studied. This bacterium was grown in media containing 1% carbon source (glucose/ coconut oil). The RLs were characterized by emulsification index (E24), thermal stability and oil spreading test. Further RLs quantification was carried out by the orcinol assay with L-rhamnose as the standard. The result showed that the highest production of RLs occurred in the presence of both coconut oil and glucose at 96 h (2.51 g/L). A stable emulsification index (E24) was observed using diesel with a maximum value of 57% at room temperature. Good stability to high temperature (120 oC) was observed when exposed at 55%. Oil displacement activity showed the presence of RLs with the highest value was at the highest RLs production. This study shows P. aeruginosa is able to produce RLs using coconut oil as the substrate and may potentially become a good source of biosurfactant for industry in the future.
Keywords: Rhamnolipids, biosurfactants, Pseudomonas aeruginosa, rhamnose, coconut oil